PENGARUH FAKTOR ATRIBUT PRODUK, PERSEPSI NILAI, DAN PENGALAMAN KONSUMEN TERHADAP MINAT BELI ULANG YANG DIMEDIASI OLEH KEPUASAN KONSUMEN (Pada Pengguna Apple iPhone di Semarang) - Mahendra, Alien Dayinta; Idris, Idris (Diponegoro Journal of Management, 2017)
The need for communication tools such as smartphones, continues to create a lot of demand and supply and also create competition between producers with other manufacturers. Similarly, an interesting phenomenon that occurs in the Apple iPhone in Indonesia, where with the increasing number of smartphone users in Indonesia Apple iPhone has decreased sales and market share. This study aims to determine the effect of product attributes, perceptions of value, and consumer experience on the interest of buying Apple iPhone products through consumer satisfaction as intervening variables.Technique that used in this research is by method of purposive sampling approach, that is consumer of Apple iPhone with category of youth in Semarang who have done upgrading its iPhone device. The sample in this research is 100 respondents. The data were collected using questionnaires. The technique of analysis and interpretation of data that used is Multiple Regression Analysis, according to the model that developed in this research, and operated through SPSS program version 22.The results showed that product attributes, perceived value, and costumer experience have a positive effect on customer satisfaction. Perceived value has the highest influence on customer satisfaction. Then, product attributes, perceived value, costumer experience, and customer satisfaction have a positive and significant effect on repurchase intention. Perceived value is the variable that has the highest effect on repurchase intention.